Biocompatible iron oxide/porous silicon nanocomposite with tunable magnetic properties. Issue 5 (31st March 2014) - Granitzer, P.; Rumpf, K.; Poelt, P.; Reissner, M.
Abstract: Iron oxide nanoparticles of 5 and 8 nm in size have been infiltrated into the pores of porous silicon. The aim is to create a superparamagnetic (SPM) nanocomposite system with maximized magnetic field induced moment. Therefore the particle size versus the superparamagnetic behaviour has been figured out. The blocking temperature TB which indicates the transition between superparamagnetic behaviour and blocked state is not only dependent on the particle size but also on the magnetic interactions between them which can be varied by the distance between the particles. The magnetic behavior of the nanocomposite has been examined with regard to the magnetic interactions between the particles within the pores. Dependent on the size but also the distance between the particles, which has been adjusted by the various concentrations, TB has been shifted. Furthermore the modification of the porous silicon template results in a change of the transition temperature due to the variation of the particle distance of adjacent pores. To fabricate distinct composite systems suitable in biomedicine the porous silicon template as well as the loading of the pores with the particles has to be adjusted. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)